2015
DOI: 10.1088/0953-2048/28/8/082001
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation betweenJc(T,H||c) andJc(77 K, 3 T||c) in Zr-added (Gd, Y)BaCuO coated conductors at temperatures from 77 down to 20 K and fields up to 9 T

Abstract: We have conducted a critical current density Jc(T, H) study over a wide temperature T from 77 down to 20 K and a magnetic field H up to 9 T on more than 50 ∼ 0.9 μm-thick REBa2Cu3O7−δ (RE = rare earth) thin films containing different concentrations of BaZrO3 (BZO). We found that, independent of the composition, there is a linear correlation between Jc(77 K, 3 T||c) and Jc(T, H||c) at T down to 20 K and H up to 9 T. Moreover, Jc(77 K, 3 T||c) is also linearly correlated to Jc(T, H||ab) below 40 K. We ascribed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
1
18
1
2
Order By: Relevance
“…By adopting a different synthesis route called MOCVD, researchers at University of Houston in USA have demonstrated that the incorporation of BZO in high volume fractions results in outstanding in-field J c performance of REBCO films which are relatively thicker (∼ 1-2 µm) [111][112][113][114][115][116]. The F pmax value of one of these composite films reached a record value of 1.7 TN/m 3 at 4.2 K together with extremely high µ 0 H irr ∼ 14.8 T (at 77 K), a value that is much higher than the µ 0 H irr ∼ 11 T of NbTi superconductor at 4.2 K [111].…”
Section: Figure 8 | (A)mentioning
confidence: 99%
“…By adopting a different synthesis route called MOCVD, researchers at University of Houston in USA have demonstrated that the incorporation of BZO in high volume fractions results in outstanding in-field J c performance of REBCO films which are relatively thicker (∼ 1-2 µm) [111][112][113][114][115][116]. The F pmax value of one of these composite films reached a record value of 1.7 TN/m 3 at 4.2 K together with extremely high µ 0 H irr ∼ 14.8 T (at 77 K), a value that is much higher than the µ 0 H irr ∼ 11 T of NbTi superconductor at 4.2 K [111].…”
Section: Figure 8 | (A)mentioning
confidence: 99%
“…Xu et al [6] performed a series of 'washing' experiments to evaluate the fraction of bitumen involved in stabilisation of W/CO emulsions. In their study, increased amounts of water were blended into bitumen diluted with toluene.…”
Section: Only a Small Subfraction Of Asphaltenes Can Be Responsible Fmentioning
confidence: 99%
“…Bitumen washing experiments-how much 'emulsifier' is in bitumen? The procedure and results are plotted using the data of Xu et al [6] which will not be discussed here. However, all of the models available in the literature consider asphaltene molecules consisting mostly of hydrophobic moieties and having no hydrophilic head in their structure.…”
Section: Different Fractions Of Crude Oil/bitumen Can Be Responsible mentioning
confidence: 99%
“…最近美国休斯顿大学的Selvamanickam团队 [17,18] 实现了25%Zr(摩尔百分比)的高浓度掺杂, 极大提升 [8,16,17] . Figure 6 (Color online) Anisotropic J c for high-density Zr doped RE123 thin film [8,18] 面和应力效应均被报道具有很好的磁通钉扎效果.…”
Section: 本课题组长期致力Tfa-mod机理和成材效率问unclassified